2016
DOI: 10.1111/jgh.13177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective CCK1 receptor antagonism on accommodation and tolerance of intestinal gas in functional gut disorders

Abstract: Inhibition of CCK1 receptors by dexloxiglumide increases intestinal gas retention and reduces abdominal symptoms in response to by intestinal gas loads. European Clinical Trials Database (EudraCT 2005-003338-16).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…An experimental gas challenge test (high-rate exogenous gas infusion directly into the jejunum) has shown that patients with functional dyspepsia who complain of bloating have impaired handling of intestinal gas, that is, gas retention, abdominal symptoms or both 165 . However, studies using abdominal CT and MRI scanning in clinical conditions could not corre late abdominal symptoms with excessive intestinal gas in these patients, as in the majority of the patients the volume and distribution of intestinal gas were within the normal ranges 166,167 .…”
Section: Gas-related Symptomsmentioning
confidence: 99%
“…An experimental gas challenge test (high-rate exogenous gas infusion directly into the jejunum) has shown that patients with functional dyspepsia who complain of bloating have impaired handling of intestinal gas, that is, gas retention, abdominal symptoms or both 165 . However, studies using abdominal CT and MRI scanning in clinical conditions could not corre late abdominal symptoms with excessive intestinal gas in these patients, as in the majority of the patients the volume and distribution of intestinal gas were within the normal ranges 166,167 .…”
Section: Gas-related Symptomsmentioning
confidence: 99%
“…To overcome these problems, our study applied very precise selection criteria through a comprehensive preentry selection process and measured symptoms during standard conditions and in response to a challenge test. Previous studies using the gas challenge test showed that patients with functional gut symptoms have impaired transit and poor tolerance to intestinal gas loads 69…”
mentioning
confidence: 99%
“…This outcome concurs with the results of a previous study evaluating the effect of Dexloxiglumide on intestinal gas transit. As observed with prucalopride, Dexloxiglumide, a CCK1 antagonist with prokinetic effects, did not reduce gas retention during the gas challenge test …”
Section: Discussionmentioning
confidence: 50%
“…Previous studies showed that these scales detect significant and consistent differences between different groups of subjects (patients and healthy subjects) in different experimental conditions (i.e. intestinal fat infusion, gastric distension, exercise, and drugs) …”
Section: Methodsmentioning
confidence: 98%